Save Nature to Survive N 11(1): 445-448, 2016 (Supplement on Agronomy) www.thebioscan.in 445 INFLUENCE OF PLANT GEOMETRY AND FERTILITY LEVELS ON GROWTH AND YIELDS OF GROWTH AND YIELDS OF GROWTH AND YIELDS OF RABI CASTOR ( CASTOR (RICINUS RICINUS COMMUNIS - R. M. SOLANKI, C. J. DODIYA,; B. J. CHATRABHUJ, M. MODHAVADIA,; B. BARAD, AND B. (The Bioscan, 2016)
A field experiment was carried out on influence of plant geometry and fertility levels on growth and yield of castor during rabi season of 2013-14 at Department of Agronomy, JAU, Junagadh. The results indicated that sowing the castor at 90cm x 45cm spacing recorded significantly higher plant population and plant height (153.5 cm).While, no. of branches plant-1(8.8) and dry matter accumulation (187.2 g plant-1), no. of spikes plant-1(8.3), length of main spike (60.4 cm) and no. of capsules per spike (64.4) as well as seed (82.2 g plant-1) and stalk yields plant-1(103.8 g plant-1) were significantly higher under wider spacing of 120cm x 60cm. Seed yield (1444 kg ha1 ), N uptake by seed (34.6 kg ha-1), phosphorus (10.6 kg ha-1) potash (12.0 kg ha-1) were significantly higher under plant geometry of 90cm x 60cm spacing. Almost all the growth characters, yield attributes, quality parameters, seed and stalk yields were found significantly higher when crop was fertilized with 100-50-50 NPK kg ha-1. It was concluded that under clayey soils of South Saurashtra agro-climatic zone for getting higher yield, rabi castor should be sown at 90 cm x 60 cm and crop should be fertilized with 100-50-50 NPK kg ha